(untitled) (Lex localis - Journal of Local Self-Government, 2025)
The study explores the impact of automation on human resource management, analyzing how it influences the evolution of work structures, skill development, and continuous training, as well as the ethical and social challenges of the future of work. The objective was to review recent advances in automation in this field through a narrative review of scientific articles published between 2020 and 2024. The results indicate that, although automation improves efficiency and competitiveness, it also presents challenges such as resistance to change, the need for ongoing training, and the lack of a regulatory framework that protects privacy and ensures fair decision-making. In conclusion, the implementation of automation requires a comprehensive strategy that combines operational efficiency with social responsibility, promoting an ethical and inclusive integration of technology that supports human talent development in a fairer and more competitive work environment.